Analysis of the Germination of Individual Clostridium sporogenes Spores with and without Germinant Receptors and Cortex-Lytic Enzymes - Wang, Shiwei; Brunt, Jason; Peck, Michael W.; Setlow, Peter; Li, Yong-Qing (Frontiers in Microbiology, 2017)
The Gram-positive spore-forming anaerobe Clostridium sporogenes is a significant cause of food spoilage, and it is also used as a surrogate for Clostridium botulinum spores for testing the efficacy of commercial sterilization. C. sporogenes spores have also been proposed as a vector to deliver drugs to tumor cells for cancer treatments. Such an application of C. sporogenes spores requires their germination and return to life. In this study, Raman spectroscopy and differential interference contrast (DIC) microscopy were used to analyze the germination kinetics of multiple individual C. sporogenes wild-type and germination mutant spores. Most individual C. sporogenes spores germinated with L-alanine began slow leakage of ~ 5% of their large Ca-dipicolinic acid (CaDPA) depot at T1, all transitioned to rapid CaDPA release at Tlag1, completed CaDPA release at Trelease, and finished peptidoglycan cortex hydrolysis at Tlys. T1, Tlag1, Trelease and Tlys times for individual spores were heterogeneous, but Trelease (Trelease - Tlag1) periods were relatively constant. However, variability in T1 (or Tlag1) times appeared to be the major reason for the heterogeneity between individual spores in their germination times. After Trelease, some spores also displayed another lag in rate of change in DIC image intensity before the start of a second obvious DIC image intensity decline of 25-30% at Tlag2 prior to Tlys. This has not been seen with spores of other species. Almost all C. sporogenes spores lacking the cortex-lytic enzyme (CLE) CwlJ spores exhibited a Tlag2 in L-alanine germination. Sublethal heat treatment potentiated C. sporogenes spore germination with L-alanine, primarily by shortening T1 times. Spores without the CLEs SleB or CwlJ exhibited greatly slowed germination with L-alanine, but spores lacking all germinant receptor proteins did not germinate with L-alanine. The absence of these various germination proteins also decreased but did not abolish germination with the non-GR-dependent germinants dodecylamine and CaDPA, but spores without CwlJ exhibited no germination with CaDPA. Finally, C. sporogenes spores displayed commitment in germination，but memory in GR-dependent germination was small, and less than the memory in Bacillus spore germination.